Menumbuhkan Rasa Peduli dan Toleransi pada Anak Sekolah Dasar Melalui Pembelajaran PKN Berbasis Kearifan Lokal - Jeriyantoro, Ferly; Elvendi, Rahmat; Nazarina, Vitara Dewi (PT Elaborium Elevasi Indonesia, 2024)
This research aims to provide a general overview of how to foster a sense of caring and tolerance in elementary school children through civics learning based on local wisdom. The research method used is literature study based on previous experts or previous research who studies concepts and collecting data from several scientific journals. Elementary school is an important stage in a child's moral and social development. Fostering a sense of caring and tolerance in elementary school age children is the basis for developing positive character and a national outlook. Citizenship education (PKn) learning can be an effective medium forachieving this goal by instilling local wisdom values related to the local cultural context. This article describes how to foster a sense of caring and tolerance in elementary school studentsthrough PKN learning based on local wisdom. This approach prioritizes contextual learning that connects PKN materialwith local values and traditions.